2017
DOI: 10.1136/bmj.j4328
|View full text |Cite
|
Sign up to set email alerts
|

Safe handover

Abstract: High quality handovers are essential for safe healthcare and are used in many clinical situations. Miscommunication during handovers can lead to unnecessary diagnostic delays, patients not receiving required treatment, and medication errors. 1 Miscommunication is one of the leading causes for adverse events resulting in death or serious injury to patients. 2 The process of handovers can be improved, and the aim of this article is to provide practical guidance for clinicians on how to do this better. How to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 13 publications
2
70
0
15
Order By: Relevance
“…[63] Extensive HIC-based research has shown that education, simulation-training, and communication tools are effective strategies for improving the quality of healthcare information transfer during transitions of care. [12] Communication tools can also be adapted to ensure they facilitate patient-centred care at the point of discharge, which takes into account patients' needs, desires and values and involves patients and carers in care/decision-making processes [12,24] In addition, several LMIC studies have evidenced that introducing patient discharge educational materials and structured disease-specific discharge planning can improve HCP to patient communication, as well as patient satisfaction, patient/carer healthcare management knowledge and post-discharge health outcomes. [64][65][66][67][68] Given the predominantly paper-based systems in use across the study settings, well-structured and standardised HCP checklists, documents and patient-held record booklets are also likely to advance the quantity and quality of essential information transferred between HCPs and between HCPs and patients and have proven successful in HIC and LMIC settings.…”
Section: Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…[63] Extensive HIC-based research has shown that education, simulation-training, and communication tools are effective strategies for improving the quality of healthcare information transfer during transitions of care. [12] Communication tools can also be adapted to ensure they facilitate patient-centred care at the point of discharge, which takes into account patients' needs, desires and values and involves patients and carers in care/decision-making processes [12,24] In addition, several LMIC studies have evidenced that introducing patient discharge educational materials and structured disease-specific discharge planning can improve HCP to patient communication, as well as patient satisfaction, patient/carer healthcare management knowledge and post-discharge health outcomes. [64][65][66][67][68] Given the predominantly paper-based systems in use across the study settings, well-structured and standardised HCP checklists, documents and patient-held record booklets are also likely to advance the quantity and quality of essential information transferred between HCPs and between HCPs and patients and have proven successful in HIC and LMIC settings.…”
Section: Next Stepsmentioning
confidence: 99%
“…[4,[8][9][10] With regard to interventions, the literature has continually advocated the timely and accurate exchange of patient-specific information to improve coordination and safety during care transitions. [11,12] Effective discharge education and documented summaries are particularly vital tools that have been shown to reduce a number of post-discharge complications and unplanned readmissions. [7,[13][14][15][16][17][18] However, in practice the delivery of discharge instructions often remains rushed and essential details for facilitating continuity of care such as diagnosis, medication, lifestyle and follow-up information are not always exchanged.…”
Section: Introductionmentioning
confidence: 99%
“…A transferência de cuidado (handoff ou handover) consiste na transferência da responsabilidade do cuidado do pa-ciente, ou grupo de pacientes, para outra pessoa ou grupo de profissionais, de forma temporária ou definitiva. 2 São dois os principais tipos de "handoffs" em saúde. O primeiro refere--se às transferências dos pacientes, em um mesmo estabelecimento assistencial ou entre diferentes serviços de saúde; no segundo tipo, o paciente permanece no mesmo local e a referência é a transferência das informações entre aqueles que têm a responsabilidade pelo seu cuidado, podendo ser durante a assistência prestada pelos profissionais e nos momentos de passagem de plantão, visando à continuidade da assistência e à segurança do paciente.…”
Section: Introductionunclassified
“…In his article on clinic letter writing, Seddon suggests that there is little formal teaching on this skill in the UK and that it is frequently poorly performed . Communication at the point of transfer of care is extremely important for continuity, and should include the patient's current state of health, diagnosis, results of investigations, treatment, a management plan and follow‐up . Transfer happens when patients are referred to secondary care, discharged from hospital or after attendance at a specialist ambulatory clinic (out‐patient department).…”
mentioning
confidence: 99%
“…8 Communication at the point of transfer of care is extremely important for continuity, and should include the patient ' s current state of health, diagnosis, results of investigations, treatment, a management plan and follow-up. 9 Transfer happens when patients are referred to secondary care, discharged from hospital or after attendance at a specialist ambulatory clinic (out-patient department). A copy of the documentation between health professionals is increasingly being given to patients.…”
mentioning
confidence: 99%